Soda anthraquinone pulping of oil palm male flower spikes - Masrol, S.R.; Ibrahim, M.H.I.; Adnan, S.; Amir Shah, M.S.S.; Main, N.M.; Esa, M.F.; Othman, M.H. (Trans Tech Publications, 2014)
This study was carried out to investigate the effect of beating process to the characteristics of pulp and paper produced from oil palm oil male flower spikes (OPMFS). OPMFS pulp was prepared according to chemical Soda-AQ pulping process. 60 gsm papersheet of oil palm male flower spiked were prepared from unbeaten and unbleached OPMFS Soda-AQ pulp. All optical, physical and mechanical characteristics were investigated according to TAPPI and MS ISO standards. OPMFS pulp recorded value of 6.42 s, 353 ml, 76.5 %, 36.7 % and 9.35 for drainage time, freeness, moisture content, screened yield percentage and Kappa number respectively...